Tinjauan Kritis Terhadap Implementasi Kurikulum Merdeka di Madrasah Ibtidaiyah : Studi Kasus di Kecamatan Purwokerto Barat - Meti Muji Pangestika; Nurfuadi (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
The Merdeka Curriculum is present as a breath of fresh air in the world of Indonesian education, providing space and flexibility for madrasas to develop operational curricula that suit their particularities and needs. The implementation of the Independent Curriculum at the madrasa level has begun to roll out, bringing new hope for the progress of madrasa education in Indonesia. This research aims to identify the implementation of the independent curriculum in Madrasah Ibtidaiyah: Case Study in West Purwokerto District. This research uses a qualitative case study approach. This approach allows researchers to understand the phenomenon under study in depth, through analysis of specific cases in relevant environments. The results of the research explain that the implementation of the Merdeka MI Curriculum in West Purwokerto District is still in its early stages and faces various challenges. More intensive efforts from various parties are needed to ensure effective implementation of the Independent Curriculum and achieve its goal of improving the quality of education at MI. The implementation of this curriculum is indeed quite behind other elementary schools, but everything will proceed according to existing plans.‎